Overcoming anxiety for dummies - Elliott, Charles H., 1948- (--For dummies., 2010)
"Get over your anxiety and create a calmer, more peaceful life. Job loss, natural disasters, terrorism--with so many things to worry about today, your anxiety levels can easily skyrocket. This engaging guide is packed with techniques you can use immediately to overcome your worries and gain control of your life. You'll pinpoint your triggers, discover the latest therapies, and make lifestyle changes that will have you feeling better fast"--P. [4] of cover.